Cone Beam Computed Tomography-Based Anatomical Assessment of the Olfactory Fossa - Costa, Andre Luiz Ferreira; Paixão, Aline Kataki [UNESP]; Gonçalves, Bianca Costa [UNESP]; Ogawa, Celso Massahiro; Martinelli, Thiago; Maeda, Fernando Akio; Trivino, Tarcila; Lopes, Sérgio Lucio Pereira De Castro [UNESP] (Hindawi, 2019)
This study aimed to investigate the olfactory fossa according to the Keros classification using cone beam computed tomography. This cross-sectional study analysed cone beam computed tomography images selected from a database belonging to a radiology centre. The scans of 174 healthy patients were analysed by using the Xoran software. Gender, age, and side were correlated with the Keros classification. The mean age of the 174 patients was 45.3 years. The most prevalent Keros classification was type II (65.52%), followed by type III (20.69%) and type I (13.79%). No significant differences were found between Keros classification and the variables age, right side (p value = 0.4620), and left side (p value = 0.5709). There were also no significant differences between gender and the variables right side (p value = 0.1421) and left side (p value = 0.2136). Based on these results, we suggest that cone beam computed tomography can be recommended for analysis of the anterior skull base. Keros type II was the most prevalent type in our sample.